Analysis of factors influencing electric energy measurement in power systems - Wenjing Yang; Gang Wang; Weitao Wu; Yan Shen; Shiqi Yin (AIP Advances, 2024)
This article focuses on summarizing and analyzing the causes of errors in electric energy meters under harmonic conditions, clarifying the relationship between errors and frequency characteristic curves, and pointing out that the positive and negative errors mainly depend on the direction of each harmonic power relative to the fundamental power, the properties of the load, the differences in physical properties of electric energy meter manufacturing and material formation, etc.